Admissibility of Fruits of Breached Evidentiary Privileges: The Importance of Adversarial Fairness, Party Culpability, and Fear of Immunity - Robert P. Mosteller (Washington University Law Quarterly, 2003)
In civil cases, breaches of attorney-client confidentiality during litigation sometimes result, not only in exclusion of communication, but also in an order prohibiting use of the information obtained from the communication in any way. In criminal prosecutions, provisions of the Constitution under certain fact patterns give protection to attorney-client confidentiality, including the attorney-client privilege, which also prohibits derivative use of the confidential communications. This Article examines two general conclusions reached by the case law. The first is the general non-protection of derivative use of the disclosure of confidential information covered by evidentiary privileges. The second concerns special situations where protection is sometimes granted. In Part II, I describe a series of cases which show the generally accepted result that out-of-court disclosures of confidential communications are not protected against derivative use. In Part III, I discuss some of the doctrinal underpinnings of this result. This analysis gives a relatively thin, but perhaps adequate, explanation of why fruits of evidentiary privilege violations are not generally protected. In Parts IV and V, I discuss special situations in which derivative evidence is sometimes excluded. In Part VI, I summarize the result: evidentiary privileges provide only limited protection for confidential communications, and one of these understandable limitations is that fruits of unauthorized disclosures are not excluded. If a stronger remedy is to be had, a justification in addition to privilege must be found to support protection of the confidence. I also recommend how privilege rules may be drafted to clarify the law as to both fruits and the somewhat related area of reporting requirements.
Keywords: Confidential communications; Fruit of the poisonous tree doctrine (Evidence); Attorney-client privilege; Evidence (Law)